Odpowiedzi

2009-12-03T16:36:17+01:00
A) (m+n)(m-2)+(m-n)(m+1) = m2-2m+mn-2n+m2-mn-n= 2m2-m-3n
b) (3x-2)(3x-2y+1)-4x(2x-3y+1) = 9x2-6xy+3x-6x+4y-2-8x2+12xy-4x= x2+6xy-7x+4y-2
c) 3(m+1)(n-2)+2(n+1)(m-2) = (3m+3)(n-2)+(2n+2)(m-2)= 3mn-6m+3n-6+2mn-4n+2mn+2m-4 = 7mn-4m-n-10
d) x(x+1)(x+2)-x(x-1)(x-2) = (x2+1)(x+2)-(-x-2) = x3+2x2+x+2-x2-2x-2x2-2x2+2x= x3-x2+x+2

Liczby za literami oznaczają do której potęgi. ;)
Najlepsza Odpowiedź!
2009-12-03T17:08:35+01:00
(m+n)(m-2)+(m-n)(m+1)=m2-2m+mn-2n+m2+m-mn-n=m+2m2-3n
b)(3x-2)(3x-2y+1)-4x(2x-3y+1)=9x2-6xy+3x-6x+4y-2-4x2+12xy-4x=5x2+6xy-7x+4y-2
c)3(m+1)(n-2)+2(n+1)(m-2)=3(mn-2m+4-2)+2(mn-2n+m-2)= 3mn-6m+12-6+2mn-2n+2m-4=5mn-4m+2-2n
d)x(x+1)(x+2)-x(x-1)(x-2)= x(x2+2x+x+2)-x(x2-2x-x+2)=x(x2+3x+2)-x(x2-3x+2)=x3+3x2+2x-x3+3x2-2x= 3x